Implications of Religious Identity Salience, Religious Involvement, and Religious Commitment on Aggression. Issue 2 (3rd April 2017) - Wright, Joshua D.; Young, Jason R.
ABSTRACT: Social identity can affect perceptions of external threats and the type of response elicited to those threats. Religion is a social identity with eternal group membership and revered beliefs and values; thus, religious identity salience, religious commitment, and religious involvement may have implications for aggressive responses to perceived threats to a person's religious identity. In a sample of 176 Christians, Muslims, and Jews, we investigated whether people respond aggressively to collective threat as a function of religious identity salience, religious commitment, and religious involvement. Religious commitment was positively related to anger only when religious identity was salient. Religious involvement was negatively related to anger and hostility only when religious identity was salient. Religious identity salience appears to act as a moderator by either enhancing perceptions of threat or by activating internal religious beliefs and values.